Making an impact: Scotland's response to tackling climate change. (2nd January 2020) - Robinson, Mike
ABSTRACT: Scotland has set some of the most stringent legislation in the world to tackle climate change. This article outlines some of the process that has brought that about. What is the role of science and what else is required to make a genuine impact on a wicked issue of this scale and complexity? Whilst the science provides a critical factual consensus around the issue, there are many stages required to actually deliver change. Critically any such issue needs to be made a public concern, and have the popular momentum necessary to persuade politicians and others to consider legislation. The process of setting legislation is prone to party politics so to be robust it needs cross party support. Even legislation is not enough, there needs to be follow through - public pressure to actually deliver against targets and create action. And for an issue as broad as climate change it needs broad sectoral and specific actions and targets, and for everyone to engage. So to truly deliver impact on such a complex wicked problem like climate change requires a complex, broad response, and at every stage, it requires an understanding of the next steps, and a relentless drive in their pursuit.